Induction of epithelial-mesenchymal transition in primary airway epithelial cells from patients with asthma by transforming growth factor-β1 - Hackett, T.L.; Warner, S.M.; Stefanowicz, D.; Shaheen, F.; Pechkovsky, D.V.; Murray, L.A.; Argentieri, R.; Kicic, Anthony; Stick, S.M.; Bai, T.R.; Knight, D.A. (AMER THORACIC SOC, 2009)
Rationale: Airway remodeling in asthma is associated with the accumulation of fibroblasts, the primary cell responsible for synthesis and secretion of extracellular matrix proteins. The process by which the number of fibroblasts increases in asthma is poorly understood, but epithelial-mesenchymal transition (EMT)may play a significant role. Objectives: To evaluate whether EMT occurs in primary airway epithelial cells (AECs), themechanisms involved, and if this process is altered in asthmatic AECs. Methods: AECs were obtained fromsubjects with asthma (n = 8) and normal subjects without asthma (n = 10). Monolayer and air-liquid interface-AEC (ALI-AEC) cultures were treated with transforming growth factor (TGF)-β1 (10 ng/ml) for 72 hours and assayed for mesenchymal and epithelial markers using quantitative polymerase chain reaction, confocal microscopy, and immunoblot. The involvement of BMP-7, Smad3, and MAPK-mediated signaling were also evaluated. Measurements and Main Results: TGF-β1-induced EMT in AEC monolayers derived from subjects with asthma and normal donors. EMT was characterized by changes in cellmorphology, increased expression of mesenchymal markers EDA-fibronectin, vimentin, α-smooth muscle actin, and collagen-1, and loss of epithelial markers E-cadherin and zonular occludin-1. Inhibition of TGF-β1-induced signaling with Smad3-inhibiting siRNA or TGF-β1-neutralizing antibodies prevented and reversed EMT, respectively, whereas BMP-7 had no effect. In ALIAEC cultures derived from normal subjects, EMT was confined to basally situated cells, whereas in asthmatic ALI-AEC cultures EMT was widespread throughout the epithelium. Conclusions: TGF-β1 induces EMT in a Smad3-dependent manner in primary AECs. However, in asthmatic-derived ALI-AEC cultures, the number of cells undergoing EMT is greater. These findings support the hypothesis that epithelial repair in asthmatic airways is dysregulated.